Efeito protetor de lactobacilos isolados de queijo Minas artesanal na infecção experimental com Salmonella enterica subsp. enterica sorovar Typhimurium - Leonardo Borges Acurcio (2016)
Dairy productshave in commonwith humanintestinalmicrobiotathe presence, indominant andsub-dominant levels, Firmicutesphylum bacteria, particularly those of theLactobacillus genus. Due to its safety use in humans, lactobacilli samples have been characterized as probiotics after isolation from dairy products, due to its better adaptation to functional food products like fermented milks. In this manner, probiotic potential from “Minas” artisanal cheese was evaluated in order to develop functional fermented milks. Results were compared to those from a knownprobiotic Lactobacillusparacasei (LP).L. casei (B5), L. plantarum (B7) andL. rhamnosus (B4 e D1) samples were tested regarding its in vitro probiotic potential againstSalmonella Typhimurium; and alsoin vivo, through a series of tests withgerm free mice colonized with lactobacilli samples infected with S. Typhimurium and also similar tests with conventional BALB/c mice. Tests included the protective effect of lactobacilli administered through fermented milk evaluating mice: survival, weight loss, translocation to target organs, ileum’s cytokines immune and microbiota modulation. Germ free mice experiments also included lactobacilli’s colonizing ability and ex vivo antagonistic effect (after lactobacilli’s passage through mice intestinal tract). Most of the experiments were conducted in two time points of infection and Lactobacillus administration. Functional fermented milk was also developed by assessing its sensory acceptance, microbiological and physical-chemical properties along its refrigerated storage, and, analternative of its delivery methodwas also tested: lyophilization.In conclusion, L. plantarum B7 and L. rhamnosus D1 samples presented themselves as the best probiotics candidates for a functional fermented milk development, especially if compared with the positive control, which presented similar results.